Association of Interleukin-2 (IL-2) Levels With Acid-Fast Bacillus (AFB) Sputum Conversion In Drug-Resistant Pulmonary Tuberculosis Patient - Gede Sasmika Suwandi; Yani Jane Sugiri; Tri Wahju Astuti; Harun Al Rasyid (Respiratory Science, 2022)
Background: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis (Mtb) which can be found on multiple organs, but mostly infect the lung. AFB smear is used to diagnose and evaluate therapy response, to show bacterial burden and the patient’s infectious status. Combination of antituberculosis drugs for a long period of time could cause poor compliance and increased risk of resistance. Mtb infection induce immune response and release cytokines, one of which is interleukin-2 (IL-2) that regulate T lymphocyte cell. Higher IL-2 levels is found on patient with high bacterial burdern.  This study aims to see the assossciation between IL-2 levels before and 30 days after DR-TB treatment, to see pre and post-treatment IL-2 levels with conversion of AFB smear, and correlation between pre-treatment IL-2 levels and AFB smear. Method: This was a cohort prospective study at RSUD dr Saiful Anwar Malang. Thirty nine DR-TB patients underwent AFB smear before and 30 days after treatment, while IL-2 levels was also measured by Enzym-Linked Immunosorbent Assay (ELISA) technique. Results: The levels of IL-2 before treatment was significantly higher compared to 30 days after treatment (P<0.001). There was no significant IL-2 levels difference between conversion and non-conversion group (P=0.23), and a weak, not-significant correlation between IL-2 levels and AFB smear (r=0.28; P=0.06). Conclusion: The levels of IL-2 was significantly higher before than after treatment and it cannot be used to determine the positivity of acid-resistant bacilli smears in the sputum of patients with DR-TB. The limited timeframe and biomarker in this study raise the possibility to observe IL-2 as well as other biomarkers after intensive phase of TB treatment for future studies.